Civic Engagement Among Youth Exposed to Community Violence: Directions for Research and Practice - Sonia Jain (Journal of Youth Development, 2019)
Historically and contemporarily marginalized youth who are disproportionately exposed to community violence are often the same youth who are less likely to be civically engaged. However, the community violence and civic engagement literatures have not yet fully explored how these experiences may be linked in young people’s lives and in relation to what other forces. Using developmental assets and ecological-transactional frameworks, we review the emerging literature on civic engagement among youth exposed to community violence and how external developmental assets and neighborhood collective efficacy may create opportunity for their increased civic engagement. We present numerous conceptually- and empirically-based hypotheses to further examine the intersections between exposure to community violence and youth civic engagement. Ultimately, we identify opportunities for intervention.